2020
DOI: 10.3390/nano10040808
|View full text |Cite
|
Sign up to set email alerts
|

3-Dimensional Porous Carbon with High Nitrogen Content Obtained from Longan Shell and Its Excellent Performance for Aqueous and All-Solid-State Supercapacitors

Abstract: Three-dimensional porous carbon is considered as an ideal electrode material for supercapacitors (SCs) applications owing to its good conductivity, developed pore structure, and excellent connectivity. Herein, using longan shell as precursor, 3-dimensional porous carbon with abundant and interconnected pores and moderate heteroatoms were obtained via simple carbonization and potassium hydroxide (KOH) activation treatment. The electrochemical performances of obtained 3-dimensional porous carbon were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Two representative peaks are detected at ∼1350 and ∼1600 cm −1 for both GQDs and FeS@GQDs, representing the defects of the carbon structure (D band) as well as in-plane stretching vibrations of sp 2 hybridization of carbon atoms (G band). 36,37 Upon comparison with the spectrum of pure FeS, it can be concluded that these two characteristic peaks are only derived from GQDs, which affirm the presence of GQDs in the FeS@GQDs composite. Besides, for FeS@GQDs, the specific value of the I D /I G is 0.88, indicating that the carbon from GQDs is highly graphitized.…”
Section: Resultsmentioning
confidence: 75%
“…Two representative peaks are detected at ∼1350 and ∼1600 cm −1 for both GQDs and FeS@GQDs, representing the defects of the carbon structure (D band) as well as in-plane stretching vibrations of sp 2 hybridization of carbon atoms (G band). 36,37 Upon comparison with the spectrum of pure FeS, it can be concluded that these two characteristic peaks are only derived from GQDs, which affirm the presence of GQDs in the FeS@GQDs composite. Besides, for FeS@GQDs, the specific value of the I D /I G is 0.88, indicating that the carbon from GQDs is highly graphitized.…”
Section: Resultsmentioning
confidence: 75%
“…Activated carbons (ACs) have been used as a conventional material for EDLC electrodes because of their intrinsic characteristic properties, such as high specific surface area, developed pore structure, and suitable surface chemical state [ 14 , 15 , 16 ]. Over the past years, much attention has been focused on transforming natural waste to worth-added ACs, such as carton [ 17 ], longan shell [ 18 ], sesame husk [ 19 ], lemon peel [ 20 ], walnut shells [ 21 ], lignocellulose [ 22 ], and palm [ 23 ]. As a result of the previous studies, it was found that there is great significance and research value in discovering low-cost and high-performance electrode materials by utilizing biowaste.…”
Section: Introductionmentioning
confidence: 99%
“…were used to make porous carbonaceous materials. [16][17][18][19][20][21] These biomass precursors produce carbons with controlled microstructure replicated from their parent biomass sources. Meng et al has recently reported such facile method of preparing supercapacitor electrodes from waste cigarette butts, which showed a high capacitance retention up to 45.75% at high current 10 Ag −1 .…”
mentioning
confidence: 99%